Profesionalac . The Professional - Kovačević, Dušan (Preco i Vans, 2003)
Duration: 01:44:00 Until recently a University professor, a bohemian writer, a member of Belgrade's intellectual circles and a passionate opponent of the Milosevic regime, Teja is now the manager of a big publishing house. One day, during a strike, a strange visitor comes uninvited to his office, carrying a big suitcase. The man turns out to be an ex-secret security agent who dedicated the last ten years of his life entirely to Teja as he continuously spied and wrote reports on him. His suitcase is full of Teja’s belongings, some of them very precious, ranging from these reports and Teja’s collected speeches to the favorite toys of Teja’s son. The rest of the film follows the long conversation between the two men, coming from different and even opposing backgrounds. Full of sudden surprises and intimate details, interrupted by numerous flashbacks, the conversation reveals how interconnected the lives of these two men were, during this long decade of Milosevic’s regime.